Survival and feeding avoidance of the eucalyptus defoliator Thyrinteina arnobia exposed to the proteinase inhibitor berenil - Marinho-Prado, J. S.; Lourenção, A. L.; Oliveira, J. A.; Guedes, R. N. C.; Oliveira, M. G. A. (Journal of Applied Entomology, 2011)
Proteinase inhibitors are recognized as potential plant protection agents against pest insects and their use is an alternative for integrated pest management. Berenil is an example of a synthetic trypsin inhibitor and its potential for use as insecticide was assessed against Thyrinteina arnobia (Stoll) (Lepidoptera: Geometridae), one of the main eucalypt defoliators in Brazil. Insect survival and its life history traits including developmen- tal time, pupa weight and viability, and life table parameters of T. arnobia were assessed in larvae reared on eucalyptus leaves containing 0.00%, 0.06%, 0.12%, 0.25%, 0.50% and 0.75% (w/v) of the synthetic trypsin inhibitor berenil. In addition, food preference and leaf consumption of T. arnobia caterpillars were also assessed. Berenil delayed larval development. Larva survival was severely affected by berenil, which also delayed larval development. Sub-lethal concentrations of berenil compromised life table parameters of T. arnobia reducing its net reproductive rate and population growth rate, while extending generation time. Berenil was also deterrent to T. arnobia and did not elicit larva compensatory feeding. The berenil activity as insecticide, repellent and antifeedant against T. arnobia suggests its potential use against eucalyptus defoliating caterpillars.
Keywords: Bis-benzamidine; Compensatory feeding; Diminazene aceturate; Life table; LT 50; Trypsin